Transient Abnormal Myelopoiesis in Down Syndrome Patients - Widya Pratiwi; Amaliyah T. Lopa; Darwati Muhadi; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Neonates with Down Syndrome (DS) have a propensity to develop the unique myeloproliferative disorder, Transient Abnormal Myelopoiesis (TAM). Transient abnormal myelopoiesis usually resolves spontaneously in < 3 months, but approximately 10% of patients with TAM die from hepatic or multi-organ failure. After remission, 20% of patients with TAM progress into acute myeloid leukemia associated with down syndrome (ML-DS). The patient was a full-term 2-day-old baby girl with a birth weight of 3300 gr. Physical examination revealed dysmorphic facial features, hypertelorism, macroglossia, and low set ears, which is a characteristic sign of DS face, skin rash, and there was no anus. On examination of peripheral blood smears and bone marrow aspiration, hematological abnormalities, and circulating blast cells were found. Early diagnosis of low-lying anorectal malformation (MAR) without fistula and down syndrome. In treating patients with TAM, it is first necessary to know whether they have trisomy 21 syndrome, then trace the existing hematological disorders to find the GATA 1 genetic mutation. The most crucial hematological problem in patients with DS is leukemia. Mutations in the GATA 1 gene and the presence of DS can result in abnormal proliferation of megakaryocytes and erythroid progenitors in the fetus and hematological abnormalities in TAM. Transient abnormal myelopoiesis can be fatal in up to 10% of patients and resolves spontaneously. Therefore, laboratory examinations are very significant, including blood tests, peripheral blood smears, supporting examinations such as bone marrow aspiration, monitoring of clinical symptoms, and close monitoring of comorbidities. Examination repeat or follow-up bone marrow aspiration is required within six months of patient follow-up to reduce the risk of further complications. In this case, a follow-up examination is highly recommended because if there are no changes, the further examination must be carried out.